Overcoming Physiological Barriers to Nanoparticle Delivery—Are We There Yet? - Thomas, Oliver S.; Weber, Wilfried (Frontiers in Bioengineering and Biotechnology, 2019)
The exploitation of nanosized materials for the delivery of therapeutic agents is already a clinical reality and still holds unrealized potential for the treatment of a variety of diseases. This review discusses physiological barriers a nanocarrier must overcome in order to reach its target, with an emphasis on cancer nanomedicine. Stages of delivery include residence in the blood stream, passive accumulation by virtue of the enhanced permeability and retention effect, diffusion within the tumor lesion, cellular uptake and arrival at the site of action. We also briefly outline strategies for engineering nanoparticles to more efficiently overcome these challenges: Increasing circulation half-life by shielding with hydrophilic polymers such as PEG, the limitations of PEG and potential alternatives, targeting and controlled activation approaches. Future developments in these areas will allow us to harness the full potential of nanomedicine.